511 Cardio-vascular remodelling during sacubitril/valsartan therapy in patients with heart failure and reduced ejection fraction. (8th December 2021) - Monosilio, Sara; Filomena, Domenico; Luongo, Federico; Neccia, Matteo; Sannino, Michele; Birtolo, Lucia Ilaria; Cimino, Sara; Benedetti, Giulia; Tonti, Giovanni; Pedrizzetti, Gianni; Fedele, Francesco; Maestrini, Viviana; et al.
Abstract: Aims: Sacubitril/valsartan (S/V) benefits in patients with heart failure and reduced ejection fraction (HFrEF) are partially related to cardiac reverse remodelling, in terms of volumes reduction and function improvement. Effects on vascular remodelling are less investigated. To evaluate cardiac and vascular remodelling in a cohort of patients with HFrEF after 6 months of therapy with S/V. Methods and results: 50 patients with HFrEF eligible to start a therapy with sacubitril/valsartan were enrolled. Clinical evaluation and standard and advanced echocardiography were performed at baseline and after 6 months of follow-up (FU). Standard left ventricular dimension and function parameters and global longitudinal strain (GLS) were calculated. Non-invasive pressure-volume curves (P-V loop) estimation was assessed with an off-line dedicated software using ST-E derived time-resolved LV volumes and brachial pressure as input. The following haemodynamic parameters were calculated based on P–V loop curves: left ventricular elastance (Ees), arterial elastance (Ea), and ventricular-arterial coupling (VAC). At 6 months F/U, a reduction of NYHA class in the vast majority of patients was detected (NYHA Class ≥ II, baseline vs. F/U = 100% vs. 50%; P < 0.001). Systolic and diastolic blood pressure were lower, in comparison with baseline values (119 ± 16 vs. 126 ± 11 mmHg; P = 0.002 and 71 ± 8 vs. 78 ± 8 mmHg; P = 0.001, respectively). At echocardiographic evaluation, left ventricular end-diastolic and end-systolic volumes decreased and ejection fraction and GLS significantly improved (Table). Moreover, a significant reduction of Ea and a significant improvement of Ees and VAC was observed (Table ). Conclusions: Therapy with S/V in HFrEF patients determines both cardiac and vascular remodelling reflecting the complex mechanisms behind clinical improvement.